2010
DOI: 10.4314/ijhr.v2i4.55427
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the knowledge of asthma among community pharmacists in Edo state

Abstract: an online international journal allowing free unlimited access to abstract and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…If pharmacists have good attitudes towards a disease state, it could influence their level of involvement with rendering patient-centred services, considering that in Nigeria, many pharmaceutical care services are not paid for [9,10]. The quality of pharmaceutical care rendered in asthma will depend on the combination of the right attitudes and knowledge base of the pathophysiology and pharmacotherapy of the disease [17]. As pharmaceutical care is patient-centred, pharmacists can encourage patients to be involved with self-management, consequently improving their adherence to long-term medication therapies [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If pharmacists have good attitudes towards a disease state, it could influence their level of involvement with rendering patient-centred services, considering that in Nigeria, many pharmaceutical care services are not paid for [9,10]. The quality of pharmaceutical care rendered in asthma will depend on the combination of the right attitudes and knowledge base of the pathophysiology and pharmacotherapy of the disease [17]. As pharmaceutical care is patient-centred, pharmacists can encourage patients to be involved with self-management, consequently improving their adherence to long-term medication therapies [17].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of pharmaceutical care rendered in asthma will depend on the combination of the right attitudes and knowledge base of the pathophysiology and pharmacotherapy of the disease [17]. As pharmaceutical care is patient-centred, pharmacists can encourage patients to be involved with self-management, consequently improving their adherence to long-term medication therapies [17]. In a study conducted at the University of Wyoming School of Pharmacy to show pharmacy students' application of their knowledge from the classroom to introductory pharmacy practice experiences, it was concluded that challenging students to think about and provide specific examples of knowledge application made the connections more explicit and also allowed students to see the relevance of the classroom portion of their education and reinforced how foundational course concepts are directly applicable to pharmacy practice [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation